Sustainable marketing dilemmas: moral, ethical, and practical in business communication perspectives - Sudirjo, Frans; Dizon, Carl C.G.; Rusmardiana, Ana; Deni, Asep; Hantono, H (Jurnal Studi Komunikasi, 2024)
Abstract In recent years, corporations’ sustainable marketing practices have gone beyond just selling mere products or services and present significant challenges. This study examines the moral, ethical, and practical challenges encountered by sustainable marketing, specifically from the standpoint of business communication. This research explains the notion of sustainable marketing and discerns its ethical dilemmas by examining the current body of scholarly literature. The discussion focuses on stakeholder theory, ethical consumerism, and communication theories. The study employs a qualitative research methodology, gathering data through comprehensive interviews and case analysis. The participants comprise marketing professionals, consumers, and companies that place sustainability as a top priority. The findings illustrate that organisations face many moral and ethical challenges while creating and executing sustainable marketing strategies. For example, challenges arise when trying to balance the desire for genuineness and openness and the success of marketing communications, as well as conflicts between moral evaluations and business goals. These challenges substantially impact the company’s communication strategy, as they are directly connected to consumer trust and brand image. This study offers valuable insights for companies creating and implementing sustainable marketing strategies. It highlights the crucial role of managing moral and ethical factors to achieve long-term success. Moreover, the discoveries can aid policymakers and regulatory agencies formulate criteria and recommendations to foster sustainable corporate practices.